2012
DOI: 10.1002/lt.23415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sleep problems and health-related quality of life among pediatric liver transplant recipients

Abstract: Rationale Among adult liver transplant recipients, sleep disturbances and fatigue are common. Sleep problems following pediatric liver transplantation may contribute to daytime fatigue and lower HRQoL. The aim of this cross-sectional study was to determine the impact of sleep problems on child HRQoL in pediatric liver transplant recipients using validated measures of sleep and quality of life. Methods Participants included 47 liver transplant recipients (LTR). The mean age of patients was 10.9 years ± 4.6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 43 publications
4
43
1
3
Order By: Relevance
“…The presence of a sleep disturbance was most frequent in the dialysis group compared to the other groups,34 while sleep disturbance was associated with a significant decrease in the overall total QoL score on the Pediatric Quality of Life Inventory (PedsQL) Version 4.0 Generic Core Scales for pre-dialysis and transplant subjects ( P = 0.002 and P = 0.001, respectively). A study of 47 pediatric liver transplant recipients investigated the impact of sleep problems (as assessed by the Pediatric Sleep Questionnaire) on HRQoL, as measured using the PedsQL 74. Sleep-related breathing disorders and excessive daytime sleepiness were prevalent, affectinĝ23% and 40% of children in the study, respectively 74.…”
Section: Short-term Health Consequences Of Sleep Disruptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of a sleep disturbance was most frequent in the dialysis group compared to the other groups,34 while sleep disturbance was associated with a significant decrease in the overall total QoL score on the Pediatric Quality of Life Inventory (PedsQL) Version 4.0 Generic Core Scales for pre-dialysis and transplant subjects ( P = 0.002 and P = 0.001, respectively). A study of 47 pediatric liver transplant recipients investigated the impact of sleep problems (as assessed by the Pediatric Sleep Questionnaire) on HRQoL, as measured using the PedsQL 74. Sleep-related breathing disorders and excessive daytime sleepiness were prevalent, affectinĝ23% and 40% of children in the study, respectively 74.…”
Section: Short-term Health Consequences Of Sleep Disruptionmentioning
confidence: 99%
“…A study of 47 pediatric liver transplant recipients investigated the impact of sleep problems (as assessed by the Pediatric Sleep Questionnaire) on HRQoL, as measured using the PedsQL 74. Sleep-related breathing disorders and excessive daytime sleepiness were prevalent, affectinĝ23% and 40% of children in the study, respectively 74. According to the parent proxy and child self-report, ~40% of participants had a substandard HRQoL.…”
Section: Short-term Health Consequences Of Sleep Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Sleepiness and fatigue are also common events in patients with chronic liver disease, which can reduce their daily function and their health-related quality of life. [19][20][21][22][23] In addition, impaired neuropsychologic and cognitive functions, such as memory, have been common in liver disease patients and transplant recipients. [24][25][26][27][28] Such deficits may lead to nonadherence to medication and its debilitating consequences, including transplant rejection, infection, and even increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep quality has also been associated with cognitive problems in other pediatric groups . Despite the significant lack of literature on sleep functioning during the pretransplant phase, research conducted with patients post‐transplantation has shown that sleep accounts for more variance than age, time since transplantation or health status in children's HRQOL . Thus, while empirical evidence reveals that disruptions in sleep are both present post‐transplantation and also associated with a wide variety of negative psychosocial outcomes, further research is needed to investigate whether similar problems exist pretransplantation, an important gap in the transplant literature.…”
Section: Introductionmentioning
confidence: 99%